1997
DOI: 10.1161/01.atv.17.4.695
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Serum Sex Hormones and Coronary Artery Disease in Postmenopausal Women

Abstract: Although sex hormones appear to be importantly involved in the development of coronary heart disease, apparently no study has yet reported an alteration in an endogenous sex hormone level in relation to coronary heart disease in women. In an attempt to determine whether any sex hormone abnormality might be a factor in the development of myocardial infarction in women, estradiol and testosterone, as well as sex hormone-binding globulin, insulin, dehydroepiandrosterone sulfate, and risk factors for myocardial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(69 citation statements)
references
References 72 publications
3
60
1
1
Order By: Relevance
“…Haffner et al (35) reported a positive association between endogenous total testosterone and systolic and diastolic blood pressure in postmenopausal women. Furthermore, hypertensive postmenopausal women are reported to have higher mean testosterone and free-to-total testosterone ratio compared with normotensive women (48). The same group demonstrated a significant association between free testosterone and blood pressure in healthy and diabetic postmenopausal women (49).…”
Section: Discussionmentioning
confidence: 92%
“…Haffner et al (35) reported a positive association between endogenous total testosterone and systolic and diastolic blood pressure in postmenopausal women. Furthermore, hypertensive postmenopausal women are reported to have higher mean testosterone and free-to-total testosterone ratio compared with normotensive women (48). The same group demonstrated a significant association between free testosterone and blood pressure in healthy and diabetic postmenopausal women (49).…”
Section: Discussionmentioning
confidence: 92%
“…Phillips et al 75 examined the correlation between testosterone and the degree of coronary atherosclerosis in a cross-sectional design among 60 patients with coronary artery disease. In this study, increasing FT levels were associated with coronary artery disease severity, independent of estradiol, BMI and other cardiovascular risk factors.…”
Section: Atherosclerosismentioning
confidence: 99%
“…52 On the other hand, androgen and sex hormone-binding globulin (SHBG) levels have been associated with risk of cardiovascular disease in pre-and postmenopausal women. 53,54 An increase in circulating androgens appears to be associated with insulin resistance and a predictor of diabetes mellitus. [55][56][57] In a previous study, we demonstrated a positive association, independent of obesity, between testosterone levels and hyperinsulinemia in postmenopausal women with no clinical evidence of cardiovascular disease.…”
Section: Estrogen Menopause and Endothelial Functionmentioning
confidence: 99%